2014
DOI: 10.1007/s10142-014-0380-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcript suppression of TaGW2 increased grain width and weight in bread wheat

Abstract: Bread wheat (Triticum aestivum L.) is a major staple crop in the world. Grain weight is a major factor of grain yield in wheat, and the identification of candidate genes associated with grain weight is very important for high-yield breeding of wheat. TaGW2 is an orthologous gene of rice OsGW2 that negatively regulates the grain width and weight in rice. There are three TaGW2 homoeologs in bread wheat, TaGW2A, TaGW2B, and TaGW2D. In this study, a specific TaGW2-RNA interference (RNAi) cassette was constructed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 29 publications
5
61
0
Order By: Relevance
“…Among these 30 genes, 26 are located in the candidate region mapped by at least one method (SLM, JLM, and GWAS) in the RIL populations and five were found to be significantly associated with kernel traits by candidate gene association mapping in a large association panel. Given the conserved functions of many of the known genes for kernel development in maize, rice, and wheat (Su et al, 2011;Hong et al, 2014;Qin et al, 2014;Jaiswal et al, 2015;Wang et al, 2015Wang et al, , 2016Ma et al, 2016;Simmonds et al, 2016), these genes represent additional candidates for kernel development across various species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these 30 genes, 26 are located in the candidate region mapped by at least one method (SLM, JLM, and GWAS) in the RIL populations and five were found to be significantly associated with kernel traits by candidate gene association mapping in a large association panel. Given the conserved functions of many of the known genes for kernel development in maize, rice, and wheat (Su et al, 2011;Hong et al, 2014;Qin et al, 2014;Jaiswal et al, 2015;Wang et al, 2015Wang et al, , 2016Ma et al, 2016;Simmonds et al, 2016), these genes represent additional candidates for kernel development across various species.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Liu et al (2015) showed that GS5 contributes to kernel size variation in maize as well as in rice. Notably, the wheat orthologs of rice GW2 and GS5 also were associated significantly with wheat kernel size and weight (Su et al, 2011;Hong et al, 2014;Qin et al, 2014;Jaiswal et al, 2015;Wang et al, 2015Wang et al, , 2016Ma et al, 2016;Simmonds et al, 2016). In addition to GS3, GW2, and GS5, many other genes controlling rice kernel size/weight have been cloned, such as genes involved in G-protein signaling (DEP1 and D1) and genes from phytohormone pathways (DST and Gn1a for cytokinin; D11, SRS5, D61, qGL3, and SMG1 for brassinosteroid; and TGW6 for auxin).…”
mentioning
confidence: 99%
“…Huang et al (2012) performed a genome-wide association study (GWAS) of flowering time and grain yield traits in a panel of 950 worldwide rice varieties and did not detect an association of OsGW2 and yield. TaGW2s in wheat are functional RING-type E3 ligases (Bednarek et al, 2012), and gene expression analysis and RNAi demonstrated that variation in them was negatively correlated with grain weight, a function that was similar to OsGW2 in rice (Su et al, 2011; Yang et al, 2012; Hong et al, 2014; Qin et al, 2014). Strong selection of certain TaGW2-6A and TaGW2-6B haplotypes occurred in global wheat breeding (Su et al, 2011; Qin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This caused premature termination and led to increased grain width and weight. However, RNAi results showed that the patterns of TaGW2 regulation on grain development might be more complex (Bednarek et al, 2012; Hong et al, 2014). Simmonds et al (2016) screened an EMS TILLING population of a tetraploid wheat cultivar “Kronos” and found that a GW2-A1 mutant allele significantly increased thousand grain weight, grain width and grain length in both durum and bread wheats.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that Sorghum has a strong adaptability to the environment, these analyses imply that Sorghum genes related to drought tolerance, salt tolerance, cytochrome, dehydrin, high temperature tolerance, disease and insect resistance can functionally enhance rice yield. This reveals that some evolutionarily homologous genes may show different functions when alien genes were expressed in different plant species (Gururani et al 2015;Hong et al 2014), and provide a novel approach to explore gene resources for plant improvement.…”
Section: Discussionmentioning
confidence: 97%